Analisis Dan Simulasi Jaringan Komputer Di SMKN 3 Tuban Menggunakan Aplikasi Cisco Packet Tracer - Amran, Ali; Ramadhan, Bima Lintang; Thoyibah, Sarirotut (Innovative: Journal Of Social Science Research, 2024)
This discussion reviews the importance of computer networks in improving the efficiency and effectiveness of organizations, especially in the context of educational institutions such as Vocational High Schools (SMK), this case study was conducted at SMK Negeri 3 Tuban, a school that has been established since 1991. Currently, the network in the school does not cover all rooms and does not have a centralized data center. The problem of different internet connections in each room causes problems in network reporting and management. To overcome this problem, good network design is needed, as well as comprehensive documentation for development and maintenance. Cisco Packet Tracer, as a network simulation software, is an important tool in designing and implementing computer networks. By using Cisco Packet Tracer, users can build complex virtual network topologies, simulate interactions between network devices, and test network configurations without the need for hardware. This study will discuss the process of network simulation with Cisco Packet Tracer, which involves building a network illusion with network components provided by the software.